2012
DOI: 10.1152/ajpcell.00207.2011
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 prevents TNF-α-mediated disruption of salivary epithelial formation

Abstract: Sjögren's syndrome is a chronic autoimmune disorder characterized by inflammation of salivary glands resulting in impaired secretory function. Our present studies indicate that chronic exposure of salivary epithelium to TNF-α and/or IFN-γ alters tight junction integrity, leading to secretory dysfunction. Resolvins of the D-series (RvDs) are endogenous lipid mediators derived from DHA that regulate excessive inflammatory responses leading to resolution and tissue homeostasis. In this study, we addressed the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
109
0
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(117 citation statements)
references
References 68 publications
7
109
0
1
Order By: Relevance
“…The PI3K has been identified as integral for regulation of ENaC-mediated AFC by insulin (32). Previous studies showed that RvD1 treatment in Par-Cro cells prevents TNF-a-mediated disruption of salivary epithelia formation and enhances cell migration and cell polarity via PI3K signaling (60). This study revealed that LY294002, a PI3K inhibitor, markedly attenuated RvD1-induced cAMP concentration and expressions of ENaC a in primary ATII cells stimulated with LPS, FIGURE 11.…”
Section: Discussionmentioning
confidence: 63%
“…The PI3K has been identified as integral for regulation of ENaC-mediated AFC by insulin (32). Previous studies showed that RvD1 treatment in Par-Cro cells prevents TNF-a-mediated disruption of salivary epithelia formation and enhances cell migration and cell polarity via PI3K signaling (60). This study revealed that LY294002, a PI3K inhibitor, markedly attenuated RvD1-induced cAMP concentration and expressions of ENaC a in primary ATII cells stimulated with LPS, FIGURE 11.…”
Section: Discussionmentioning
confidence: 63%
“…Preincubation of cells with RvD1 abolished tight junction and cytoskeletal disruption caused by TNF-␣ (30). Furthermore, RvD1 enhanced lumen formation and cell polarity in Par-C10 cells cultured under two-and threedimensional conditions through Akt signaling (30). These results indicate that RvD1 has the potential to improve salivary epithelial integrity in vitro and in vivo.…”
mentioning
confidence: 72%
“…These mediators exhibit anti-inflammatory and proresolving actions to block cell damage and enhance tissue repair after injury or infection (9,16,18,26). Previously, we showed that resolvin D1 (RvD1) prevents inflammatory responses and enhances tissue integrity in the rat parotid cell line Par-C10 (30). Preincubation of cells with RvD1 abolished tight junction and cytoskeletal disruption caused by TNF-␣ (30).…”
mentioning
confidence: 99%
“…signaling in several tissues, including corneal, renal, and salivary epithelium (Hassan and Gronert, 2009;Li et al, 2010;Odusanwo et al, 2012). The enzymes PLA 2 and LOX have been widely studied in many cell systems (Appendix Discussion).…”
Section: Hmsg (Ss) Negativementioning
confidence: 99%